Dakwah Cerdas di Era Modern - Basit, Abdul (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2013)
Tremendous changes of society in practicing their religious teachings require the modifications in proselytizing techniques. This paper explains how the proselytizing is to be delivered effectively in the modern era. It suggests that there are four principles of proselytizing in the contemporary era. First, consider the proselytizing as a science and research object to meet the needs of society. Second, change the paradigm of proselytizing into Islamic communication science by synthesizing theories of communication with da’wah theories based on Islamic teachings. Third, upgrade your knowledge of preaching and your skills of imple–mentting information technology in proselytizing. Fourth, utilize a variety of popular communication media as much as possible.Keywords: paradigm of da’wah science, modern technology, social changes, Muslim cleric.————————————————————————–Tulisan ini berupaya menjelaskan bagaimana cara berdakwah yang cerdas di era modern, dan berpendapat bahwa ada empat hal yang bisa dilakukan dalam berdakwah di era kontemporer, yakni pertama, menjadikan dakwah sebagai objek ilmu yang dapat diteliti dan dikembangkan sesuai dengan kebutuhan dan tuntutan masyarakat. Kedua, mengubah paradigma ilmu dakwah menjadi ilmu komuni–kasi Islam dengan cara mensintesiskan teori-teori ilmu komunikasi dengan teori-teori dakwah yang bersumber dari ajaran Islam. Ketiga, menyiapkan da’i yang mampu ber–adaptasi dengan perkembangan IPTEK. Keempat, meman–faatkan berbagai media komunikasi dan informasi yang ba–nyak dipergunakan oleh masyarakat.Kata Kunci: paradigm ilmu dakwah, teknologi modern, perubahan masyarakat, da’i.